Knowledge, attitude and practice toward anemia among mothers of adolescent girls in Puducherry, South India: a community-based cross-sectional study - Rajeswari Ramachandran; Jeyagowri Subash; Jeevaharini Harikrishnan; Narmatha Nagappan; Sowmiya Pazhanisamy (International Journal Of Community Medicine And Public Health, 2026)
Background: Anemia remains a major public health problem among adolescent girls in India, with adverse effects on growth, cognitive development, and future maternal health. Mothers play a key role in influencing adolescents’ dietary and health behaviors. This study assessed the knowledge, attitude, and practice (KAP) regarding anemia among mothers of adolescent girls in Puducherry and examined their association with selected demographic variables. Methods: A community-based descriptive cross-sectional study was conducted among 160 mothers of adolescent girls selected through convenience sampling. Data were collected using a structured knowledge questionnaire, attitude scale, and practice checklist. Descriptive statistics and Chi-square tests were used for data analysis. A p value